Investigation of the effect of the reagent suite in froth flotation of a Merensky ore - Moimane, Tiisetso Makheane (Department of Chemical Engineering, 2016)
The mining industry is faced with a challenge to develop efficient and economically feasible processing routes owing to the depletion of high-grade ores, and the ever increasing demand for precious metals for a wide range of applications. The valuable minerals, PGMs (Platinum Group Minerals) and BMS (Base Metal Sulphides) in the ores are extracted through the aid of chemical reagents (activators, collectors, depressants, frothers, modifiers) which are added to the flotation circuits to facilitate the separation between these minerals and the undesired gangue minerals present in the ore. The process is made complex by many surface reactions taking place, the existence of secondary and interactive effects among the flotation reagents, as well as the surface liberation of the minerals. Owing to the stringent regulations around water usage, concentrator plants are left with no option but to recycle water within their operations. This practice leads to accumulation of pollutants, such as organics, flotation reagents residues, dissolved ions, etc., which will likely have an influence on the chemical environment of the process, and subsequently will bear an impact on the overall metallurgical performance of the concentrator. This makes the process even more intricate, making it difficult to account for the behaviour of the chemical reagents, as well as making it virtually impossible to precisely assess their individual contribution to the overall flotation performance. Hence it is of crucial importance to adopt a holistic approach when investigating the effects of the chemical parameters in a flotation process. This is a flotation chemistry study that adopted a two-level-four-factor (24) factorial experimental design to evaluate the simultaneous effects of the chemical parameters, with particular reference to collector, depressant, frother, and ionic strength of the synthetic plant water, as well as determining the possible interactive effects between the chosen parameters. This investigation was made possible by conducting batch flotation tests on a PGM-bearing ore from the Merensky reef of the Bushveld Igneous Complex. Sodium isobutyl xanthate (SIBX), a polysaccharide, namely guar gum, and a polyglycol ether, namely Dowfroth 250 were used as the collector, depressant and frother, respectively. These are the typical chemical reagents the dosages of which tailored in the PGM industry for the processing of the ores. The metallurgical performance indicators used were solids, water, copper and nickel recoveries as well as copper and nickel grades.